2000
DOI: 10.1007/s004280000262
|View full text |Cite
|
Sign up to set email alerts
|

Centriacinar region inflammatory disease in young individuals: a comparative study of Miami and Los Angeles residents

Abstract: Semiquantitative measurements of chronic inflammation of the centriacinar region (proximal acinus of lung) were compared between 20 Miami and 18 Los Angeles residents (ages 11-30 years) for whom smoking histories were available. Mean extent and severity scores of four lung sites were higher for Los Angeles than Miami residents, with effect of city statistically significant for extent (P=0.02). Also, maximum scores for extent and severity by city were significantly greater for Los Angeles residents (P=0.02, eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The radiological abnormalities and spirometric changes suggest the development of small airway disease with the accompanying in ammatory picture and bone marrow effect (23). Sherwin has shown centriacinar in ammatory disease in young individuals residing in Los Angeles and demonstrated signi cant differences in lung in ammation scores between Miami and Los Angeles residents (102). Thus, chronic lung parenchymal in ammation seems widespread in Mexico City and occurs in at least some young urban residents of the United States.…”
Section: Discussionmentioning
confidence: 99%
“…The radiological abnormalities and spirometric changes suggest the development of small airway disease with the accompanying in ammatory picture and bone marrow effect (23). Sherwin has shown centriacinar in ammatory disease in young individuals residing in Los Angeles and demonstrated signi cant differences in lung in ammation scores between Miami and Los Angeles residents (102). Thus, chronic lung parenchymal in ammation seems widespread in Mexico City and occurs in at least some young urban residents of the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Accessioned lungs that were not suitable for processing or histopathological examination were excluded from the study. The respective transplantation services carried out all next-of-kin interviews in accord with a protocol modified from the independent investigation noted earlier [10]. Demographic data were not made available to the principal investigator until the pathological studies had been completed.…”
Section: Demographic Studymentioning
confidence: 99%
“…What is needed to help answer the question of uniformity is information on the topographical distribution of eosinophils within cartilaginous bronchi, but to date, there are no reports affording that information. An opportunity to obtain quantitative data on topographical distributions of bronchial eosinophilia was provided by an independent and ongoing medical examiner autopsy study of young Los Angeles (LAC) and Dade-Miami County (DMC) residents who died suddenly from violence [10]. Feasibility was supported by an earlier subjective study [11] of a similar group of individuals where a 10% incidence of bronchial eosinophilia was found in association with an apparent highly variable topographical distribution of eosinophils.…”
Section: Introductionmentioning
confidence: 99%
“…A similar study comparing young, recently deceased patients in Los Angeles and Miami found higher levels of pulmonary centriacinar inflammation in the Los Angeles residents. 41 A large study of children demonstrated a significant decrease in the forced expiratory volume in 1 second (FEV1) in those patients living in areas with high concentrations of DEPs. 42 Another pediatric study concluded a dose-dependent inverse association exists between the carbon content of airway macrophages and FEV1 for children living in urban areas with significant diesel exhaust exposure.…”
Section: Pulmonary Effectsmentioning
confidence: 99%